Empowering Citizens, Engaging the Public - Eisfeld, Rainer. author. aut Link
XXVI, 199 p.
Keywords: “Eisfeld’s analysis of political science and its limits offers a bold framework for reforming the discipline in this century. Eisfeld asks us to look at foundational issues of democracy in the broadest possible terms.” —Dianne Pinderhughes, former APSA President, University of Notre Dame “Of major significance for the debate over 21st century political science, impressive in its intellectual scope.” —Marian Sawer, former AAPSA President, Australian National University “An intellectual commitment to ‘thinking big’, and a bold vision of the social sciences’ ‘promise’ - freeing citizens from feeling trapped through public engagement.” —Matthew Flinders, former PSA President, University of Sheffield “A remarkable project, pulled off with a grace and balance that belie the complexity and controversy of the issues Eisfeld addresses.” —Leslie A. Pal, former CPSA Board Member, Carleton University, Ottawa This book is the first comprehensive study to respond to the ongoing debates on political sciences’s fragmentation, doubtful relevance, and disconnect with the larger public. It explores the implications of the argument that political science ought to become more topic-driven, more relevant and more comprehensible for "lay" audiences. Consequences would include evolving a culture of public engagement, challenging tendencies toward liars’ rule, and emphasizing the role of “large” themes in academic education and research, the latter being identified as those areas where severe democratic erosion is occurring – such as escalating income and wealth disparities pushing democracy towards plutocracy, ubiquitous change triggering insecurity and aggression, racist prejudice polarizing societies, and counter-terrorism strategies subverting civil liberties. Political science needs to address these pressing problems ahead of other issues by in-depth research and broadly accessible public narratives, including solution-orientated normative notions. This need provides the final justification for evolving a discipline where problems would take priority over methods and public relevance over sophisticated specialization. Rainer Eisfeld, Professor Emeritus of Political Science at Osnabrück University, Germany, taught at UCLA as a Visiting Professor. He has represented IPSA’s research committees on the IPSA Executive Committee, and has also served on the Board of Trustees of the Buchenwald/Mittelbau-Dora Concentration Camp Memorial. .